Food Insecurity and Coping Mechanism During COVID-19 Pandemic: Evidence from Indonesia - Pratiwi, Ira Eka (Universitas Islam Internasional Indonesia, 2024)
This study provides empirical evidence with respect to identifying whether the coping mechanism adopted by households in Indonesia significantly influences food security during the COVID-19 pandemic. The data used was from the fourth round of high-frequency monitoring data of COVID-19 impact on households from the World Bank (www.microdata.worldbank.org), which was collected between November 3rd – 15th, 2020 through the phone-based survey. By employing the logit regression model and controlling for demography characteristics such as gender, age, and education level, this study confirms that reducing non-food consumption has been effectively lowering the probability of food insecurity in all forms of indicators, including “were hungry” (3.3 percentage points), “went without eating” (2.0 percentage points), “unable to eat nutritious food” (6.6 percentage points), “food shortage” (9.6 percentage points), and “eat less” (5.6 percentage points). Additionally, households who relied on saving had a lower probability of 13.7 percentage points of being unable to eat nutritious food, while households who received assistance from the government had a lower chance of 2.4 percentage points of experiencing hunger during the pandemic. This study emphasizes that temporary strategies or short-term coping mechanisms such as relying on support from relatives, taking loans, and engaging in additional income-generating activities, as well as reducing food consumption may not contribute effectively to food security, instead, these types of coping mechanisms may exacerbate food insecurity. The findings of this study offer several implications in regard to enhancing the capacity of households to cope with the difficulties during crises as well as policy implications to design effective interventions in dealing with future shocks.